Improved blood oxidative status is not associated with better memory performance in postmenopausal women receiving Tualang honey supplementation - Shafin, Nazlahshaniza; Zakaria, Rahimah; Othman, Zahiruddin; Hussain, Nik Hazlina Nik (Research Publisher Inc., 2014)
We examined association between the changes in blood oxidative stress level/activity and the changes in memory performance in postmenopausal women receiving Tualang honey (TH). The verbal learning and memory performances of thirty nine postmenopausal women were assessed using the Malay version of the Auditory Verbal Learning Test (MVAVLT) and their oxidative stress levels/activities were determined using commercially available kits before and 16 weeks after TH supplementation. The plasma glutathione peroxidase (GPx) and catalase (CAT) activities were considerably increased but the 4-hydroxynonenal (4-HNE) level was notably decreased after 16 weeks of TH supplementation. There were positive correlations between the changes in plasma GPx and the changes in trial A6 scores (r = 0.48, P < 0.05) and between the changes in plasma CAT and the changes in recognition score (r = 0.32, P < 0.05). TH supplementation for 16 weeks reduced blood oxidative stress but most of the changes in blood oxidative stress level/activity were not significantly correlated with the changes in memory performance.